Analisis Kualitas Air Tanah di Desa Beru Kecamatan Jereweh Kabupaten Sumbawa Barat - Efendi, Junaidi; Hilmi, Amirul; Ulfa, Andi Maria (Universitas Kristen Maranatha, 2024)
Water is a very important basic need for human life. The fulfillment of water needs in Beru Village is highly dependent on groundwater, which is extracted by digging wells. Due to the community’s dependence on the availability of well water, it is very important to monitor and assess groundwater quality in Beru Village. The lack of related research makes this research very important to do. The purpose of this study is to analyze groundwater quality in Beru Village, Jereweh District, West Sumbawa Regency. Water quality test parameters use the parameters include pH, temperature, conductivity, TDS, and DO. The average values of each parameter sequentially are 7.07; 30.18OC; 752.71 µS/cm; 377.91 mg/L; and 4.83 mg/L. On average, the quality of groundwater is classified as good and meets the required quality standards. Based on pollution index calculation, water quality based on parameters pH (PIj=0.92) and TDS (PIj=0.497) is classified as good, while water quality based on parameters temperature (PIj=1.079) and DO (PIj=1.162) is categorized as slightly polluted but relatively safe to use for sanitary hygiene needs.